Resenha do livro "Vassouras, A Brazilian Coffee County, 1850-1900" - Ianni, Octavio (Revista de História, 1959)
STEIN, Stanley J. Vassouras, A Brazilian Coffee County, 1850-1900 Harvard University Press, Cambridge, Massachusetts, 1957, XVI-314 págs.